Potential shared neoantigens from pan-cancer transcript isoforms - Jirapat Techachakrit; Aijaz Ahmad Malik; Trairak Pisitkun; Sira Sriswasdi (Scientific Reports)
Abstract Isoform switching in cancer is a prevalent phenomenon with significant implications for immunotherapy, as actionable neoantigens derived from these cancer-specific events would be applicable to broad categories of patients, reducing the necessity for personalized treatments. By integrating five large-scale transcriptomic datasets comprising over 19,500 samples across 29 cancer and 54 normal tissue types, we identified cancer-associated isoform switching events common to multiple cancer types, several of which involve genes with established mechanistic roles in oncogenesis. The presence of neoantigen-containing peptides derived from these transcripts was confirmed in broad cancer and normal tissue proteome datasets and the binding affinity of predicted neoantigens to the human leukocyte antigen (HLA) complex via molecular dynamics simulations. The study presents strong evidence that isoform switching in cancer is a significant source of actionable neoantigens that have the capability to trigger an immune response. These findings suggest that isoform switching events could potentially be leveraged for broad immunotherapeutic strategies across various cancer types.